Fitness costs of resistance to insecticide pymetrozine combined with antimicrobial zhongshengmycin in Nilaparvata lugens (Stål) - Feng, Xupiaoyang; Li, Danting; Wang, Hongfeng; Yu, Xiaoping; Shentu, Xuping (Frontiers in Physiology, 2023)
The brown planthopper, Nilaparvata lugens (Stål), is a major pest of rice crops, and its control is critical for food security. Pymetrozine has been recommended as an alternative to imidacloprid for controlling N. lugens, but the pest has developed high resistance to it, making its prohibition and restriction urgent. To address this issue, we conducted a study using a mixture of pymetrozine and zhongshengmycin with the effective ratio of 1:40, to evaluate the fitness costs in N. lugens. Our results showed that N. lugens had a relative fitness of 0.03 under this ratio, with significantly reduced longevity, female and male adult periods, total pre-oviposition days, and fecundity. Moreover, the expression levels of the uricase gene (EC1.7.3.3) and farnesyl diphosphate farnesyl transferase gene (EC2.5.1.21) were reduced in N. lugens. These genes are involved in urea metabolism and steroid biosynthesis pathway, respectively, and their suppression can interfere with the normal nutritional function of N. lugens. Our study demonstrates that the combination of chemical insecticides and antimicrobials can delay the development of resistance and improve the efficiency of pest control. This information is valuable for researchers developing management strategies to delay the development of pymetrozine resistance in N. lugens.